A framing analysis on COVID-19 management strategy by Health Minister “Terawan” published on Detik.com and Kumparan.com - Nurindra, Dyah Ayu (Penerbit Universiti Kebangsaan Malaysia, 2021)
On March 2nd, 2020, the first case of COVID-19 in Indonesia was announced. Dr. Terawan Agus Putranto, who is the Health Minister of the Kabinet Indonesia Maju [Onward Indonesia Cabinet], received public scrutiny over his attitude in responding to the COVID-19 pandemic. Coverage of Terawan's handling of the COVID-19 outbreak appeared in the news many times, including on online news organisations detik.com and kumparan.com. Mass media framing is considered very important in the delivery of news, particularly so in a disruptive era. This descriptive interpretive qualitative study aims to illustrate how detik.com and kumparan.com framed Health Minister Terawan and his management of the COVID-19 outbreak in Indonesia. Data was obtained from online news articles relating to Terawan as the Health Minister and the management of COVID-19 outbreak in Indonesia from March 2nd –31st, 2020. The Zhongdang Pan and Gerald M. Kosicki framing model is used as the method of analysis and contains four framing device structures, namely syntax, script, theme, and rhetoric. The results of this study indicate that neither the word choices in headlines nor the manner in which facts are presented by detik.com caused controversy or offended Terawan. Furthermore, the word choices in headlines and the manner in which facts are presented by kumparan.com are considered to slightly offend Terawan without causing controversy. Overall, there is no significant difference in the framing of Terawan and his management of the COVID-19 outbreak in Indonesia between Detik.com and Kumparan.com.